Functional performance of the combines in subsystems-projects "fields-combines" - Сидорчук, Олександр Васильович; Комарніцкий, Сергій Петрович; Жуль, Сергій Григорович (Eastern-European Journal of Enterprise Technologies, 2012)
The method of predicting the parameters of the requirements flow of combine to unload the hopper and hourly average performance of each of them in a given field is developed. The trends of change in the average values ​​of these parameters are opened